Retransmissions versus FEC plus interleaving for real-time applications a comparison between CDPA and MC-TDMA cellular systems. - Borgonovo, F. (IEEE Journal on selected areas in communications)
The capacity of mobile cellular systems is mainly limited by cochannel interference. Commonly in multiple carrier-time division multiple access (MC-TDMA) systems, like the global system for mobile (GSM) communications, the interference noise is first reduced by means of channel clustering and slow frequency hopping. The residual interference, characterized by a level varying slot by slot, causes errors in burst which are spread with bit interleaving and fought with correcting codes for random errors. With real-time services like voice, no other error control technique, such as automatic repeat request (ARQ), is usually adopted. An alternative approach is given by capture division packet access (CDPA) where transmissions are spread in time adopting a dynamic slot assignment (DSA), and errors are dealt with a retransmission mechanism. In this paper, we present a comparison of this two approaches, and using a simple theoretic capacity analysis, we justify the better performance of CDPA. Moreover, by the delay performance analysis, we prove that in spite of its retransmission mechanism, CDPA is effective also with delay constrained services